Anti-allodynic effect induced by curcumin in neuropathic rat is mediated through the NO-cyclic-GMP-ATP sensitive K+ channels pathway - Tracy Pastrana-Quintos; Giovanna Salgado-Moreno; Julia Pérez-Ramos; Arrigo Coen; Beatriz Godínez-Chaparro (BMC, 2020)
Abstract Background Recent studies pointed up that curcumin produces an anti-nociceptive effect in inflammatory and neuropathic pain. However, the possible mechanisms of action that underline the anti-allodynic effect induced by curcumin are not yet established. The purpose of this study was to determine the possible anti-allodynic effect of curcumin in rats with L5-L6 spinal nerve ligation (SNL). Furthermore, we study the possible participation of the NO-cyclic GMP-ATP-sensitive K+ channels pathway in the anti-allodynic effect induced by curcumin. Methods Tactile allodynia was measured using von Frey filaments by the up-down method in female Wistar rats subjected to SNL model of neuropathic pain. Results Intrathecal and oral administration of curcumin prevented, in a dose-dependent fashion, SNL-induced tactile allodynia. The anti-allodynic effect induced by curcumin was prevented by the intrathecal administration of L-NAME (100 μg/rat, a non-selective nitric oxide synthase inhibitor), ODQ (10 μg/rat, an inhibitor of guanylate-cyclase), and glibenclamide (50 μg/rat, channel blocker of ATP-sensitive K+ channels). Conclusions These data suggest that the anti-allodynic effect induced by curcumin is mediated, at least in part, by the NO-cyclic GMP-ATP-sensitive K+ channels pathway in the SNL model of neuropathic pain in rats.